Risk factors for early radiation-induced heart damage in patients undergoing pulmonary SBRT - Tingcui Li; Dan Zhu; Ming Cui (Echo Research and Practice)
Abstract Background Stereotactic body radiotherapy (SBRT) is superior to conventional radiotherapy for the treatment of lung tumors but can lead to radiation-induced heart damage (RIHD). Its risk factors have not been clarified. The purpose of our study was to determine the risk factors for early RIHD in patients undergoing pulmonary SBRT. Methods We prospectively included patients who planned to receive pulmonary SBRT at our center from January 2020 to May 2021. Two-dimensional speckle tracking echocardiography was performed within 2 months after radiotherapy. The diagnostic criterion for early RIHD was a decrease in global longitudinal strain by ≥ 15% from baseline. Logistic regression was used to explore the risk factors for early RIHD. Results A total of 108 patients were included in the study. The overall incidence of early RIHD in the cohort was 41.7%. Significant risk factors, including maximum heart dose, anthracycline use and hypertension, were independently associated with early RIHD, with ORs of 1.058 (95% CI: 1.028–1.089; p < 0.001), 3.524 (95% CI: 1.296–9.577; p = 0.014), and 4.284 (95% CI: 1.424–12.890; p = 0.010), respectively. The cutoff of the maximum heart dose was 27.0 Gy in patients who received anthracycline and 29.3 Gy in those who did not. Conclusions Among patients receiving pulmonary SBRT, the maximum heart radiation dose, the use of anthracycline drugs and hypertension are independently associated with the occurrence of early RIHD. These findings could be applied to predict early RIHD and screen for high-risk patients. Individualized cardiac dose limitations may be helpful in improving the long-term prognosis of pulmonary SBRT patients.